Development of spectrofluorimetric stability indicating method for determination of naratriptan hydrochloride in pharmaceutical dosage form - Rizk, Mohamed; Sultan, Maha; Elshahed, Mona; Ali, Mourad (European Journal of Chemistry, 2018)
A stability indicating spectrofluorimetric method is developed for the determination of naratriptan hydrochloride in pharmaceutical formulation. The proposed method is based on investigation of the native fluorescence spectral behaviour of the drug in aqueous phosphate buffer (pH = 7.0±0.2).The fluorescence intensity is measured at 355.0 nm after excitation at 230.0 nm. The fluorescence-concentration plot is linear over the concentration range 8.0-80.0 ng/mL, with lower detection limit of 2.6 ng/mL and quantification limit of 7.6 ng/mL. The method is successfully applied to the analysis of the studied drug in its commercial tablet. Furthermore, the proposed method is applied in dissolution study of tablet; the results are in good agreement with those obtained with the reference method. The proposed method is approved to be a stability-indicating assay after exposure of the drug to different forced degradation conditions, such as acidic, alkaline and oxidative conditions, according to International Conference on Harmonization guidelines.